1987
DOI: 10.1002/polb.1987.090250601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crack tip sharpness on the strength of vulcanized rubbers

Abstract: SynopsisThe effect of crack tip sharpness on crack propagation in vulcanized rubbers has been studied. For very sharp cracks, tearing is found to occur on a small scale at very low energies not far above the threshold required for the onset of mechanical crack growth. The "small-scale" tearing energies show relatively little variation for rubbers that differ widely in tear strength as normally measured. Thus the latter property appears to be strongly influenced by variations in the ability of rubbers to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 34 publications
(4 reference statements)
5
58
0
Order By: Relevance
“…Mixed mode crack propagation studies on mammalian tissue (Purslow, 1983a b;Pereira et al, 1997) and rubber (De and Gent, 1996;Greensmith and Thomas, 1955;Lake and Yeoh, 1978;Lake and Yeoh, 1987) suggest that the measured toughness J IC is sensitive to the type of test performed. Scissor cutting tests and razor cutting tests maintain a sharp crack tip and give a low-toughness value.…”
Section: Toughnessmentioning
confidence: 98%
“…Mixed mode crack propagation studies on mammalian tissue (Purslow, 1983a b;Pereira et al, 1997) and rubber (De and Gent, 1996;Greensmith and Thomas, 1955;Lake and Yeoh, 1978;Lake and Yeoh, 1987) suggest that the measured toughness J IC is sensitive to the type of test performed. Scissor cutting tests and razor cutting tests maintain a sharp crack tip and give a low-toughness value.…”
Section: Toughnessmentioning
confidence: 98%
“…Previous studies [13][14][15][16] showed that the measured fracture energy is significantly reduced when a sharp blade is applied at the tip of a crack. This phenomenon was attributed to a constant crack-tip diameter, which equals the sharpness of the blade, in the process of fracture.…”
Section: Cutting Testmentioning
confidence: 98%
“…It has been pointed out that the crosslinking density of EPDM plays an important role in reducing the tensile set and increasing the tensile strength of TPEs. 8 Swollenstate 13 C-NMR spectroscopy has been successfully applied to estimate the crosslinking densities in EPDM-based TPEs. 11 Recently, a comprehensive review article on the EPDM/PP TPEs prepared by dynamic vulcanization was published.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have suggested that the puncture process associated with medical needles involves a cutting phenomenon . Other studies have related cutting to the fracture energy G c of the material (Lake and Yeoh 1987;Cho and Lee 1998). According to the energy balance of fracture mechanics, the energy necessary to create a new fracture surface, the fracture energy G s , can be expressed by (Felbeck and Atkins 1996):…”
Section: Resultsmentioning
confidence: 99%